Development and Implementation of Android-Based Interactive E-Modules to Improve Mathematical Problem-Solving Skills at Secondary Schools Hamid Khan Pulau Pinang Malaysia - Khairunnisa, Eka; Suryaningsih, Fitria (Journal of Science and Mathematics Education, 2025)
This study aims to develop and implement Android-based interactive e-modules to enhance mathematical problem-solving skills among students at Secondary Schools Hamid Khan, Pulau Pinang, Malaysia. The main issue in mathematics learning at the school lies in students’ low engagement and the lack of interactive learning media aligned with technological developments. This research adopts a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The e-modules were developed with interactive features such as tutorial videos, adaptive exercises, and automated assessments. The study involved 60 upper secondary students divided into experimental and control groups. Data were collected through mathematical problem-solving tests, student response questionnaires, and classroom observation. The results indicated a significant improvement in the mathematical problem-solving abilities of students in the experimental group compared to the control group. Student responses toward the e-modules were highly positive, with the majority expressing that the modules helped them understand mathematical concepts more enjoyably and deeply. The study concludes that Android-based interactive e-modules are effective in enhancing the quality of mathematics learning and can serve as an innovative alternative in digital education at the secondary school level.